THE USE OF VARIOUS HYDROCHLORIC ACID CONCENTRATION LEVELS ON THE RABBIT BONE GELATIN QUALITY - Gumilar, Jajang; Suryaningsih, Lilis; Fri Setia, Dandin (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
Rabbit meat production continues to increase every year. An increase rabbit meat production causes bone production to increase as well. Rabbit bones can be used further to add value. The protein content in the bones is collagen. Collagen can be hydrolyzed to produce gelatin. The gelatin demand is high enough so the rabbit bones can be utilized as gelatin raw material. The purpose of this study was to determine the effect of hydrochloric acid concentration on the rabbit bone gelatin and to determine the concentration of hydrochloric acid which produced the best gelatin quality. The design of the research was the Complete Random Design. The results of the study were analyzed by analysis of variance followed by Duncan's Multiple Range Test (DMRT) if the results of previous tests yielded significantly different results. This study used five treatments of hydrochloric acid concentration (P1 = 3%, P2 = 4%, P3 = 5%, P4 = 6%, P5 = 7%) with three replications. The use of hydrochloric acid concentration did not affect the water content but did affect the yield, ash content, pH, and viscosity of rabbit bone gelatin. The use of hydrochloric acid with a concentration of 6% produced the best quality of rabbit bone gelatin with an average yield value of 3.92 ± 0.40%, water content 10.23 ± 0.89%, ash content 4.70 ± 0.07%, pH 3.75±0.17, and viscosity 10.63±0.32 mP.